Interference with the Autophagic Process as a Viral Strategy to Escape from the Immune Control: Lesson from Gamma Herpesviruses - Santarelli, Roberta (J Immunol Res, 2015)
We summarized the most recent findings on the role of autophagy in antiviral immune response. We described how viruses have developed strategies to subvert the autophagic process. A particular attention has been given to Epstein-Barr and Kaposi's sarcoma associated Herpesvirus, viruses studied for many years in our laboratory. These two viruses belong to γ-Herpesvirus subfamily and are associated with several human cancers. Besides the effects on the immune response, we have described how autophagy subversion by viruses may also concur to the enhancement of their replication and to viral tumorigenesis.